1987
DOI: 10.1007/bf01314419
|View full text |Cite
|
Sign up to set email alerts
|

Replication of mumps virus in mouse: transient replication in lung and potential of systemic infection

Abstract: A mumps virus strain, which replicated in mouse lung after aerosol inhalation, was obtained by selective replication of a wild strain in L929 cells and by further passaging in mice by intraperitoneal inoculation. All of infected mice survived and rechallenge of the survived mice with the same virus resulted in no virus growth in the lung. Treatment of infected mice with antiserum against interferon (IFN) or asialo GM1 delayed virus clearance from lung. Mice at 5 weeks of age were also sensitive to the virus as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Inflammation of the testis leads to hypofertility and testicular atrophy, which causes sterility that is usually transient but permanent in rare cases (8). Mumps virus replicates in the testes of mice (14), and a morphological study of the testes of patients infected with mumps virus showed degeneration of the seminiferous epithelium (4). The disruption of spermatogenesis may be a consequence of a drop in testosterone secretion by Leydig cells.…”
mentioning
confidence: 99%
“…Inflammation of the testis leads to hypofertility and testicular atrophy, which causes sterility that is usually transient but permanent in rare cases (8). Mumps virus replicates in the testes of mice (14), and a morphological study of the testes of patients infected with mumps virus showed degeneration of the seminiferous epithelium (4). The disruption of spermatogenesis may be a consequence of a drop in testosterone secretion by Leydig cells.…”
mentioning
confidence: 99%
“…Based on previous work by others, mumps viruses do not productively replicate in mice nor cause any symptomatology [17, 18]. Similar problems with other RNA viruses, such as Junin virus, Dengue, and Ebola has been overcome by using mice lacking the IFN-α/β receptor (IFN-α/βR −/− ) [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Mice, as cost-efficient animals, are models for many human pathogens. However, mumps viruses are not known to replicate well or cause illness in adult mice (7,12,13). One mouse fibroblast cell-adapted mumps virus strain was reported to transiently replicate in the lungs of mice and might have circulated in the animal during infection (13).…”
mentioning
confidence: 99%
“…However, mumps viruses are not known to replicate well or cause illness in adult mice (7,12,13). One mouse fibroblast cell-adapted mumps virus strain was reported to transiently replicate in the lungs of mice and might have circulated in the animal during infection (13). In most studies, mice were used to evaluate immune responses induced by different attenuated strains of mumps virus (12) or to evaluate memory B cell responses after MMR vaccination (14).…”
mentioning
confidence: 99%